1981
DOI: 10.1037/0096-1523.7.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Configural effects in perceived pointing of ambiguous triangles.

Abstract: Five experiments examined the influence of configural variables on perceived pointing of ambiguous (equilateral) triangles. The amount of time required to see the triangles point in specified directions was measured for single triangles and linear configurations of multiple triangles. The results show that perceived pointing is biased toward directions that are coincident with or perpendicular to the configural line. Perceptual interference occurs when the configural line biases pointing away from the correct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
66
1
5

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 9 publications
10
66
1
5
Order By: Relevance
“…Resultsfrom both tasks showed systematic biases due to the relation between the direction of motion and the structure ofthe triangle: Motion along an axis ofsymmetry (parallel to a possible direction of pointing) facilitated perceived pointing along that axis. However, motion along a side of the triangle (perpendicular to a possible direction of pointing) produced no such facilitative effect, in contrast to analogous perpendicular effects in previous studies using static patterns (Palmer, 1980;Palmer & Bucher, 1981, 1982. These results are interpreted as evidence that event symmetry is an important stimulus characteristic underlying directional biases due to motion.…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…Resultsfrom both tasks showed systematic biases due to the relation between the direction of motion and the structure ofthe triangle: Motion along an axis ofsymmetry (parallel to a possible direction of pointing) facilitated perceived pointing along that axis. However, motion along a side of the triangle (perpendicular to a possible direction of pointing) produced no such facilitative effect, in contrast to analogous perpendicular effects in previous studies using static patterns (Palmer, 1980;Palmer & Bucher, 1981, 1982. These results are interpreted as evidence that event symmetry is an important stimulus characteristic underlying directional biases due to motion.…”
contrasting
confidence: 56%
“…We hoped to find out which ones, if any, induced systematic biases in perceived pointing. The second experiment employed a more rigorous, performance-oriented "interference" paradigm (Palmer & Bucher, 1981, 1982 to provide converging evidence about the same issues.…”
Section: Base Alignment Axis Alignmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Attneave observed that these triangles are perceived alternatively to point in any of these three directions with approximately equal preference. The preferences for these directions have been investigated in relation to motion (Bucher and Palmer 1985), texture (Palmer and Bucher 1982), and configuration (Palmer and Bucher 1981). Spontaneous switching between these directions has been reported for prolonged viewing conditions (Attneave 1968(Attneave , 1971).…”
mentioning
confidence: 99%